2009
DOI: 10.1007/s10535-009-0023-1
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium-induced oxidative damage and antioxidant responses in Brassica juncea plants

Abstract: Indian mustard (Brassica juncea L. cv. Vitasso) plants exposed to 10, 30, 50 and 100 μM of Cd for 5 d in hydroponic culture were analysed with reference to the distribution of Cd 2+ , the accumulation of biomass and antioxidants and antioxidative enzymes in leaves. Cd induced a decrease in plant biomass. The maximum accumulation of Cd occurred in roots followed by stems and leaves. Cd induced a decrease in catalase (CAT) and guiacol peroxidase (GPX) activities but an increase in ascorbate peroxidase (APX) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 17 publications
5
38
0
Order By: Relevance
“…Higher Cd accumulation in roots than in shoots of B. juncea cv. Vitasso was ascertained also by Markovska et al (2009). Translocation of Cd to shoot was similar in both species (see shoot/root content quotient in Table 2) which corresponds with the results of Marchiol et al (2004).…”
Section: )supporting
confidence: 78%
See 1 more Smart Citation
“…Higher Cd accumulation in roots than in shoots of B. juncea cv. Vitasso was ascertained also by Markovska et al (2009). Translocation of Cd to shoot was similar in both species (see shoot/root content quotient in Table 2) which corresponds with the results of Marchiol et al (2004).…”
Section: )supporting
confidence: 78%
“…Brassica juncea L. cv. Vitasso has short vegetation period from 40 to 60 days, can be grown in a wide range of soil types (Markovska et al 2009), and is potentially usable in phytoremediation (Pollard et al 2002).…”
Section: Materials and Growth Conditionsmentioning
confidence: 99%
“…Both DHAR and MDHAR activities were induced with Cd treatments (Figure 3 E-F, G-H). The increase in MDHAR activity under Cd treatments have been reported by Markovska et al (2009) in B. juncea and by Romero-Puertas et al (2007) in Pisum sativum plants. Decrease in DHAR activity under Cd treatment (10 μM) in Ceratophyllum demersum has been reported by Arvind and Prasad (2005).…”
Section: Discussionmentioning
confidence: 70%
“…Cd is not an essential nutrient for plants, and it can accumulate at higher levels in aerial organs (Wang et al, 2007;Zou et al, 2008), inducing phytotoxicity manifested in leaf roll, chlorosis, growth reduction, and eventually death (Benavides et al, 2005;. It has been demonstrated that Cd affects a wide range of physiological and metabolic activities in plants: for example, Chl a and b content (Mobin and Khan, 2007), the activities of photosynthetic carbon reduction cycle enzymes (Burzyński and Zurek, 2007), mineral distribution (Wang et al, 2007;Zou et al, 2008), photosynthetic processes Chen et al, 2010) and oxidative stress Markovska et al, 2009). The intensity of the effects depends on the species, metal concentration and duration of exposure (Benavides et al, 2005).…”
Section: Introductionmentioning
confidence: 99%